Pengaruh Konten Kreatif Instagram Dan FOMO (Fear Of Missing Out) Terhadap Keputusan Pembelian Skintific Dengan Customer Engagement Sebagai Variabel Mediasi - Brian Assidiq; Agus Widarko; Ita Athia (UNIVERSITAS ISLAM MALANG, 2026)
Abstract The rise of social media has significantly impacted consumer behavior, especially Generation Z, who actively use Instagram. This research looks at the effects of Instagram creative content and Fear of Missing Out (FOMO) on purchase decisions, with customer engagement as a mediating variable. By employing a quantitative method, data was gathered using surveys of Generation Z students at Universitas Islam Malang who had purchased Skintific products. To find both direct and indirect links between variables, path analysis was used. The findings demonstrate that creative content and FOMO significantly increase customer engagement, which in turn positively affects purchase decisions. Customer engagement also mediates the correlation between creative content, FOMO, and purchase decisions. These results emphasize the significance of creating engaging Instagram content and strengthening customer engagement to enhance purchase decisions in digital marketing strategies targeting Generation Z Keywords: : Customer Engagement, Fear of Missing Out, Generation Z, Instagram Creative Content, Purchase Decision